2014
DOI: 10.1094/pdis-02-14-0142-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report on the Occurrence of a New Pathotype, 714, of Plasmopara halstedii (Sunflower Downy Mildew) in Hungary

Abstract: Downy mildew of sunflower, caused by Plasmopara halstedii (Farlow) Berlese et de Toni, is an economically important disease in Hungary and much of Europe. The known pathotypes (races) of the pathogen influence the resistance genes (Pl genes) incorporated into new sunflower hybrids to manage the disease. There are at least 36 pathotypes of P. halstedii worldwide (3), but the number of races is increasing rapidly. In 2010, race 704 was identified in Hungary for the first time (2). Race 704 has been reported to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In the last years of the survey, four races, 70471, 71461, 70571 and 71571, were detected with high virulence complexity which overcome Pl 6 and even Pl 15 genes. Beside these results, new occurrences of races 704 and 714 have been reported from Hungary (Bán et al ., ,) as well as a recent prevalence of race 714 in France (Virányi et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last years of the survey, four races, 70471, 71461, 70571 and 71571, were detected with high virulence complexity which overcome Pl 6 and even Pl 15 genes. Beside these results, new occurrences of races 704 and 714 have been reported from Hungary (Bán et al ., ,) as well as a recent prevalence of race 714 in France (Virányi et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…In 2007 the global number of P. halstedii races reached 36 (Gulya, ), 24 of which were reported in North America, 20 in Europe, 10 in Africa, and 5 races in both South America and Asia. In the following years, new races were found in Europe; 721 and 731 that were discovered in Bulgaria during 2007/8 (Shindrova, ), race 704 (Bán et al ., ) and 714 (Bán et al ., ) in Hungary and race 774 in France (Gascuel et al ., ). Recently, Virányi et al .…”
Section: Introductionmentioning
confidence: 99%
“…The first high virulent pathotype (704) was isolated in 2010 by Rudolf et al [ 22 ] from two sunflower fields in Hungary. In the following years, our research team confirmed the increased distribution of pathotype 704 in the country [ 27 ] and the emergence of three new P. halstedii pathotypes, 714, 724, and 734 [ 13 , 14 , 28 ] (New records are separated from previously published records by bold isolate numbers in Table 3 .). Previously, pathotype 724 was only identified from Hungary, but according to our present results, it was also detected in Romanian samples in 2019.…”
Section: Discussionmentioning
confidence: 56%
“…Downy mildew on cultivated sunflowers was first recorded in the USA in the 1920s (Young & Morris, ). Cultivation of open‐pollinated sunflower varieties that were highly susceptible to Ph, both in Europe and North America, helped the rapid spread of the disease (Virányi, ; Sedlářová et al ., , ; Bán et al ., ; Anonymous, ; Virányi et al ., ) and caused several severe outbreaks (Zimmer, ; Göre, ). Therefore sunflower downy mildew has been declared a quarantine pathogen in the European Union since 1992 (Delmotte et al ., ).…”
Section: Introductionmentioning
confidence: 99%